Management of Spontaneous Pneumothorax in Children: A Systematic Review and Meta-Analysis - Miscia, Maria Enrica; Lauriti, Giuseppe; Lisi, Gabriele; Riccio, Angela; Lelli Chiesa, Pierluigi (European Journal of Pediatric Surgery, 2020)
Introduction Management of primary spontaneous pneumothorax (PSP) is mainly based on adults. Data are controversial with regards to its management in children. We aimed to assess: (1) the length of hospital stay (LOS) between conservative management (i.e., observation with O2 administration), aspiration/chest drain, and surgical management; (2) the risk of recurrence after nonsurgical treatment versus surgery; (3) the risk of recurrence in the presence of bullae.Materials and Methods Using a defined search strategy, three independent investigators identified all the studies on the management of PSP in children. Case reports, opinion articles, and gray literature publications were excluded. The study was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A meta-analysis was performed using RevMan 5.3. Data are expressed as mean ± SD.Results Of 3,089 abstracts screened, 95 full-text were analyzed, 23 were included in the quantitative analysis, and 16 were included in the meta-analysis (1,633 patients). LOS was similar between conservative and surgical management (6.2 ± 0.8 days vs. 5.9 ± 1.4 days; p = ns). Recurrence of PSP was significantly higher among children with a nonsurgical management (32%) versus those surgically treated (18%; p = 0.002). The incidence of recurrence was slightly higher in patients managed by aspiration/chest drain (34%) compared with those with a conservative management (27%; p = 0.05). Risk of recurrence in patients with or without documented bullae was not significantly different (26 vs. 38%, respectively; p = ns).Conclusion Given the lack of a standardized management of pediatric PSP, the present study seems to demonstrate a better outcome in children treated with surgery as first-line of management.Level of Evidence This is a Level III study.
Keywords: spontaneous pneumothorax; children; systematic review; meta-analysis